1.3 mJ, 396 MHz hybrid chirped pulse amplification system laser with fiber-Yb:YAG crystal rod - Zhili Li; Ting Luo; Xinjian Pan; Liming Liu; Shixiang Xu (Results in Physics, 2025)
A high-repetition-rate, hybrid chirped pulse amplification system (CPA) is presented, utilizing fiber pre-amplifier in conjunction with a Yb:YAG crystal thin rod as the main amplifier. The repetition frequency of the laser pulses is reduced from 396 MHz to several tens of kilohertz, which is necessary for burst pulse applications in industrial processing. Following the hybrid chirped amplification, the laser pulses are compressed using a grating pair compressor that provides a dispersion match with the stretcher composed of chirped fiber Bragg gratings (CFBGs). The system achieves an average output power of 32.5 W, a burst energy of 1.3mJ, and a pulse duration of 720 fs. Notably, the spectral gain narrowing effect was observed, with the narrowest spectral width recorded at 2.7 nm. The findings indicate that the nonlinear and thermal effects, which frequently arise in laser amplifiers, are effectively managed within this system. This configuration shows significant potential for improving efficiency in industrial processing as it is capable of delivering high-energy, high-power pulsed laser output. Thereby establishing it as a preferred option for ensuring optimal reliability and stability in ultrafast lasers for industrial applications.